Uji Efek Renal Repair Ekstrak Etanol 70% Akar Dan Batang Putri Malu (Mimosa Pudica) Pada Tikus Putih Jantan Galur Wistar Yang Diinduksi - Soleh, Triono, Dr. dr. EM Sutrisna, M. Kes, Riandini Aisyah, S.Si, M.Sc (2015)
Background : Putri malu (Mimosa pudica) is known to has efficacy because it contains many active compounds one of them is flavonoid which is its function is as a good antioxidant, the main function of antioxidant is in cells regeneration. Putri malu is a plant that has the effect of the renal repair, the mechanism of it is regenerate glomeruli and the other kidney cells damage because of increasing levels of ureum and creatinin in blood. Levels of ureum creatinin that rises will add workload in the kidneys resulting in the damage of kidney cells. There has been no research about the effect of renal repair root and stem of putri malu. Therefore, researchers was conducted the effects the renal repair ethanol 70 % roots and stems extract putri malu (Mimosa pudica) in male white mice Wistar strain induced alloxan. Objective : To determine effects the renal repair ethanol 70 % roots and stems extract putri malu (Mimosa pudica) induced alloxan. Methods : The Study used pretest and posttest with control group design for 11 days. A thirty Rattus norvegicus devided into 3 groups randomly induced alloxan. Group A, given extracts of roots a dose of 600 mg/kgBB, Group B, given extract a shaft of with a dose of 600 mg/kgBB, and Group C treated by aquadest. Result : Based on One Way Anova statistic assay, it showed that probability value of ureum was P = 0,002 and creatinine was P = 0,000. LSD with post hoc test was conducted to continue this assay and resulted that ureum value of root to stem group, root to control and stem to control was 0,830 ; 0,002, and 0,001, respectively. While creatinine was 0,141 ; 0,000, and 0,000, respectively. Conclusion : Ethanol 70 % roots and stems extract of putri malu (Mimosa Pudica) can reduce kidney damage by decreasing ureum levels and creatinin in the mice blood that induced alloxan.